Kepemimpinan Kyai Dalam Memberdayakan Kewirausahaan Santri - Hayana, Nur; Wahidmurni, Wahidmurni (J-MPI (Jurnal Manajemen Pendidikan Islam), 2019)
Pondok Pesantren have contributed a lot in national development, including in terms of creating an independent workforce. One of them is to equip santri with entrepreneurial competencies. The aim of the study was to reveal the Kyai's strategy in empowering entrepreneurship of santri, Kyai's leadership style in empowering santri entrepreneurship, and the implications of Kyai's leadership in empowering santri entrepreneurship. A qualitative approach to the type of multisite case study was applied in the study. Data was collected by conducting in-depth interviews, participant observation and documentation studies. Data analysis uses data reduction, data presentation and conclusion drawing. The technique of checking the validity of research findings using triangulation of data sources and data collection techniques. The results showed that the strategies implemented by the Kyai in empowering santri entrepreneurship were carried out by giving an example of entrepreneurship, providing field learning, giving assignments in the pesantren business unit and providing motivation; the leadership style applied is a blend of democratic, transformative and charismatic leadership styles; the implication is that santri have a spirit of entrepreneurs.